2022
DOI: 10.1021/acs.inorgchem.1c03674
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Pressure-Induced Optical Materials: Europium-Doped Hafnium Silicates with a Khibinskite Structure for Optical Pressure Sensors and WLEDs

Abstract: Ultrasensitive pressure-induced optical materials are of great importance owing to their potential applications in optical pressure sensors. However, the lack of outstanding pressure sensitivity, observable color evolution, and structure reliability limits their further development in both practical applications and luminescence theory. To overcome the above problems, an enlightening methodology is proposed to explore the high sensitivity and phase stability of hafnium silicate K2HfSi2O7 (KHSO) phosphor with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…6(a). After exponential fitting and calculation, we found that these decay curves can be accurately fitted using a double exponential equation: 52–54 where I is for emission intensity, τ 1 and τ 2 are the decay times of the exponential components, and both A 1 and A 2 are constants. The average decay times for x in the range 5–25 are 2.09 ms, 2.55 ms, 2.66 ms, 2.67 ms, and 2.31 ms, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6(a). After exponential fitting and calculation, we found that these decay curves can be accurately fitted using a double exponential equation: 52–54 where I is for emission intensity, τ 1 and τ 2 are the decay times of the exponential components, and both A 1 and A 2 are constants. The average decay times for x in the range 5–25 are 2.09 ms, 2.55 ms, 2.66 ms, 2.67 ms, and 2.31 ms, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…6(a). After exponential fitting and calculation, we found that these decay curves can be accurately fitted using a double exponential equation: [52][53][54]…”
Section: Decay Time and Quantum Efficiencymentioning
confidence: 99%
“…The similar profiles from ∼220 to 300 nm can be assigned to the host absorption, and the unique strong absorption band in the region of 360–500 nm only appear in KSBO: 1.25%Eu 2+ sample indicating the attribution to the 4f 7 →4f 6 5d transition of Eu 2+ 25 . To further identify the absorption edge, the Kubelka–Munk absorption coefficient ( K / S ) relationship is applied as follows 26 : FRhvnbadbreak=A()hvEg\begin{equation}{\left[ {{\rm{ }}F{\rm{ }}\left( {{R}_\infty } \right){\rm{ }}hv{\rm{ }}} \right]}^n = {\rm{ }}A\left( {hv{\rm{ }} - {\rm{ }}{E}_g{\rm{ }}} \right)\end{equation}where A is the proportional constant, and ℎν stands for the photon energy. The ratio of absorption coefficient to reflection coefficient is determined as (𝑅 ∞ ).…”
Section: Resultsmentioning
confidence: 99%
“…The similar profiles from ∼220 to 300 nm can be assigned to the host absorption, and the unique strong absorption band in the region of 360-500 nm only appear in KSBO: 1.25%Eu 2+ sample indicating the attribution to the 4f 7 →4f 6 5d transition of Eu 2+ . 25 To further identify the absorption edge, the Kubelka-Munk absorption coefficient (K/S) relationship is applied as follows 26 :…”
Section: Electronic Band Structure Of Ksbomentioning
confidence: 99%
“…Currently, to optically monitor pressure with luminescent materials, the spectroscopic parameters, such as the band position (line shift), the emission lifetime and the bandwidth are mainly used, as their values may change monotonously with pressure. [23,[30][31][32] Utilizing the band shift under high-pressure conditions, the sensitivity (dλ/dP) of commonly used ruby-based sensors (Al 2 O 3 :Cr 3+ ) is around 0.35 nm GPa −1 . [33,34] Yichao Wang et al reported the BaLi 2 Al 2 Si 2 N 6 :xEu 2+ phosphors for optical pressure sensing, exhibiting sensitivity of dλ/dP ≈ 1.58 nm GPa −1 .…”
Section: Introductionmentioning
confidence: 99%